2020
DOI: 10.3390/cancers12113219
|View full text |Cite
|
Sign up to set email alerts
|

Past, Present and Future of Oncolytic Reovirus

Abstract: Oncolytic virotherapy (OVT) has received significant attention in recent years, especially since the approval of talimogene Laherparepvec (T-VEC) in 2015 by the Food and Drug administration (FDA). Mechanistic studies of oncolytic viruses (OVs) have revealed that most, if not all, OVs induce direct oncolysis and stimulate innate and adaptive anti-tumour immunity. With the advancement of tumour modelling, allowing characterisation of the effects of tumour microenvironment (TME) components and identification of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(67 citation statements)
references
References 191 publications
(224 reference statements)
1
66
0
Order By: Relevance
“…Importantly, reovirus-activated NK cells are specific for malignant cells and do not degranulate against non-malignant hepatocytes 41 or other immune cell populations present in mixed PBMC cultures (data not shown), in keeping with the excellent safety profile of reovirus in clinical trials. 42 Moreover, while the human in vitro system used in this study involved allogeneic MM cell lines, we have previously confirmed that NK cells can degranulate against autologous tumor cells, 16 and here we show that murine NK cells degranulate against syngeneic 5TGM1 cell targets ( online supplemental figure S3D ). Furthermore, cell death within 4 hours is characteristic of NK cell-mediated killing on addition of PBMC and we have previously validated the role for NK cells in these well-defined in vitro assays.…”
Section: Discussionsupporting
confidence: 65%
“…Importantly, reovirus-activated NK cells are specific for malignant cells and do not degranulate against non-malignant hepatocytes 41 or other immune cell populations present in mixed PBMC cultures (data not shown), in keeping with the excellent safety profile of reovirus in clinical trials. 42 Moreover, while the human in vitro system used in this study involved allogeneic MM cell lines, we have previously confirmed that NK cells can degranulate against autologous tumor cells, 16 and here we show that murine NK cells degranulate against syngeneic 5TGM1 cell targets ( online supplemental figure S3D ). Furthermore, cell death within 4 hours is characteristic of NK cell-mediated killing on addition of PBMC and we have previously validated the role for NK cells in these well-defined in vitro assays.…”
Section: Discussionsupporting
confidence: 65%
“…Reoviruses demonstrate an inherent propensity to infect transformed cells with such disrupted physiology [ 12 ]. The release of progeny viruses often leads to host cancer cell death, which makes it a lytic life cycle; the process is known as “oncolysis” [ 71 ]. Direct oncolysis by viral replication is facilitated using various signaling pathways involving TNFα, Fas ligand (FasL), TNF-related apoptosis-inducing ligand (TRAIL), ROS and others [ 72 , 73 , 74 ], and can lead to different types of cell death in different cancers [ 67 , 75 ].…”
Section: Reovirus-based Dual-prong Anticancer Actions and Myeloid Cellsmentioning
confidence: 99%
“…A multitude of viral vectors have been explored for their potential oncolytic properties, particularly as a method of delivering targeted treatment to sites of malignant disease [19]. The ability to genetically modify these viruses to target and exploit essential oncogenic signaling pathways has kept them at the forefront of immuno-oncology research [20]. This particular vulnerability triggers selective replication of the viral genome and directly contributes to furthering the oncolytic process.…”
Section: Conclusion/future Directionsmentioning
confidence: 99%
“…The tumor-associated antigens that are released into the tumor microenvironment are phagocytosed by antigen-presenting cells, thus initiating the process of T-cell-mediated adaptive anti-tumor immunity. In addition to the anti-tumor response, the presence of the oncolytic virus also triggers a concurrent anti-viral response, and regulatory mechanisms become crucial to ensuring a controlled immune response, including the upregulation of immune checkpoints [20].…”
Section: Conclusion/future Directionsmentioning
confidence: 99%